Holistic Layer of the Enterprise Architecture on the Basis of Process-Driven Organization - Stepan Alexa; Vaclav Repa (Complex Systems Informatics and Modeling Quarterly)
Growing complexity of the enterprise ecosystem along with the existence of legacy approaches in the organization can result in a number of challenges when maintaining the solid baseline of its information assets. The digital industry has, over past two decades, passed through rapid evolution triggered both by availability of new technologies, and business as well as operating and funding models. These enablers have direct impact on the way that organizations design and execute their business processes in order to maintain the alignment between their capabilities and targets. This trend implies that enterprises and organizations need to remain flexible by maintaining the alignment of their business and their infrastructure in a dynamically changing and integrated ecosystem. It has been widely recognized that the enterprise architecture as well as the process driven approaches provide tools used by organizations to explain how business, resources and other elements within the organization are related to each other. This article discusses the role, and associated value, that the enterprise architecture and process driven approach have when describing what constitutes the enterprise. At the same time it elaborates on principles and constructs of the model of the holistic layer of the enterprise architecture on the basis of process driven approach. The proposed model aims to combine a unified view on infrastructure and behavior of the enterprise with lean principles in order to identify and focus on key elements of the enterprise.